Effect of ownership change and growth on firm value at the issuance of bonds with detachable warrants - Oh, Sekyung; Kim, Woo Sung (Journal of Business Economics and Management, 2016)
This paper empirically explores the relationship between the issuance of bonds with detachable warrants and firm value and the relationship between growth and firm value at the issuance of such bonds. Twelve years of data for 721 issuances of 451 Korean listed firms are analyzed using a panel regression model. We find that at the issuance of bonds with detachable warrants, the change in firm value is strongly correlated with large shareholder ownership concentration and issuance form, and the effect of growth on firm value is strongly correlated with the cash flow condition of the issuing firm. The results indicate that the ownership structure and the cash flow condition of the issuing firm and the form of issuance are important determinants of the relationship between the issuance of bonds with detachable warrants and firm value; these results are applicable to an analysis of the mixed market reactions of convertible bonds or bonds with warrants issues across different countries. They also offer the policy implication that the Korean government’s decision to entirely prohibit firms from issuing bonds with detachable warrants may have been excessive.